Ecological studies on bryophytes along altitudinal zonations in Genting Highlands, Peninsular Malaysia / Cheah Yih Horng - Cheah , Yih Horng (2017)
The present research investigated the species richness of epiphytic and terrestrial bryophytes along an altitudinal gradient on a mountain in Peninsular Malaysia. Bryophyte communities found at different elevations and their association with various ecological factors was analyzed. Study plots were laid along the altitudinal gradient at 300 m intervals, resulting in six different elevation zones, from the foothills to the summit of Gunung Ulu Kali (1758 m), in the Genting Highlands. A total of 453 bryophyte species comprising 283 liverworts and 170 mosses were recorded from 18 study plots of 0.04 hectare each, with three study plots at each elevation zone. A total of 106 liverwort species reported in the present study are new to Peninsular Malaysia, of which 54 species are new to the country (including Peninsular Malaysia, Sabah and Sarawak). In general, liverworts were more diverse than mosses in all elevation zones. Epiphytic bryophytes were largely represented by Calymperaceae, Lejeuneaceae, Lepidoziaceae, Lophocoleaceae, Plagiochilaceae, and Sematophyllaceae, whereas ground bryophytes were mainly Aneuraceae, Lejeuneaceae, Lepidoziaceae, Lophocoleaceae, and Sematophyllaceae. A few species were recorded exclusively at certain zones or even particular study plots, and could be good indicators where they occurred. In general, epiphytic bryophytes showed higher species evenness than ground bryophytes, and most of the bryophyte species, both epiphytic and terrestrial, were found to occupy only small areas, or present at low abundances. Epiphytic liverworts dominated the montane forests, especially the summit region, whereas epiphytic mosses were more abundant in the lowlands. A similar difference was observed for ground bryophytes species, except at the summit zone where both liverwort and moss coverage values were very similar in two of the study plots. Statistical analyses showed that host-epiphyte or substrate preferences for bryophytes were not important factors most of the time, suggesting that bryophyte assemblages within a forest were principally influenced by microclimatic conditions. Cluster dendrograms revealed that the bryophyte communities investigated in the present study were clustered according to the different forest types present along an altitudinal gradient, viz., the lowland forest, transition between lowland and lower montane forests, the lower montane forest, and the upper montane forest. Ambient temperature and relative humidity are apparently important factors in determining the distribution of different bryophyte species.